Potential of macang (Mangifera foetida) bark extract on antioxidant levels and pro-apoptotic proteins in rats (Rattus norvegicus) exposed to polystyrene nanoplastics - Safitri, Maya; Nurbani, Farah Annisa; Lulhaq, Hidayaturrohman Mulvi; Jamaluddin, Faiz; Wulandari, Khairani Resti; Pramudya, Manikya; Dewi, Firli Rahmah Primula; Lim, Vuanghao; Hayati, Alfiah (Penerbit Universiti Kebangsaan Malaysia, 2025)
Nanoplastics in the environment primarily originate from contaminated aquatic animals, detergent waste, and cosmetic products, which can accumulate in the body through ingestion, inhalation, and skin exposure. This accumulation poses significant health risks, including reproductive health disruptions. This study aims to assess the potential of Mangifera foetida (macang) bark extract as an antioxidant to enhance immune and reproductive health in rats exposed to polystyrene nanoplastics (NP). Twenty-five male rats were divided into five groups: a control group, a negative control (10 μL/kg NP), and three treatment groups receiving 10 μL/kg NP with 50, 100, or 200 mg/kg of M. foetida extract for 35 days. The DPPH assay showed an IC50 value of 22.176 ppm, indicating strong antioxidant activity of the bark extract. Exposure to NP reduced the levels of endogenous antioxidant enzymes (SOD and CAT) and increased pro-apoptotic proteins (Bax and Caspase-3), affecting the histological structure and size of the testes. Treatment with M. foetida extract restored SOD and CAT levels while reducing Bax and Caspase-3 levels, improving histological structure by increasing the epithelium thickness and seminiferous tubule diameter. These findings suggest that M. foetida bark extract has potent antioxidant properties and can mitigate NP-induced toxicity, making it a promising protective agent.